Ni-Cu bimetallic catalysts on Yttria-stabilized zirconia for hydrogen production from ethanol steam reforming. (15th November 2020) - Chen, Fangyuan; Tao, Yongwen; Ling, Huajuan; Zhou, Cuifeng; Liu, Zongwen; Huang, Jun; Yu, Aibing
Graphical abstract: Abstract: One of the key challenges in catalytic ethanol steam reforming (ESR) is the ease of deactivation of the catalysts caused by metal sintering and carbon deposition. In this study, bimetallic Ni-Cu catalysts supported on Yttria stabilized zirconia (YSZ) have been prepared for ESR. Bimetallic Ni-Cu catalysts were active for ESR and the addition of Cu can improve the Ni performance and stability of the catalysts in ESR. Adding a small amount of Cu to the catalyst successfully led to formation of Cu-Ni alloy, which is efficient for improving reducibility of the catalyst. However, high Cu content limited the activity of the catalysts due to the lack of exposed active sites of Ni and Cu. In ESR, Ni was proposed to be responsible for CC bond cleavage while Cu was for the promotion of WGS. YSZ has very limited role in reducing coke formation as the catalyst support though it has high surface oxygen mobility, which is indicated by the serious deactivation by coke formation on Ni/YSZ monometallic catalyst. However, Cu addition on bimetallic Ni-Cu catalysts is proved to be effective to improve stability of the catalysts by reducing coke deposition. Among all the catalysts, Cu1 Ni9 /YSZ exhibited superior performance and stability with negligible activity loss during 20 h ESR reaction at 450 °C and 650 °C, respectively.